Cross-Ownership: A Device for Management Entrenchment?. (22nd March 2016) - Levy, Marc; Szafarz, Ariane
Abstract: By artificially inflating capital and creating own shares, cross-ownership can be a key device for managerial entrenchment. This article proposes a game-theoretical method to measure the extent of shareholder expropriation through cross-ownership. By properly accounting for cross-ownership linkages, we show how managers can seize indirect voting rights, and so insulate their firms from outside control. Significant examples of cross-ownership are found not only in civil law countries, but also in the US mutual fund industry. We apply our method to Germany's Allianz Group. This article paves the way to better regulatory appraisal of management entrenchment through cross-ownership.